Novel stereoselective sulfur ylide epoxidation reaction catalyzed by ferrocenylsulfide - 汪磊 黄志真 (Journal of Zhejiang University. A. Science, 2005)
A range of ferrocenyl sulfides are synthesized and screened. Among them l-a-methysulphoferrocenyl ethyl acetate and l-a-methysulphoferrocenyl alcohol are found to be unexpected catalysts, which is first reported mediating in sulfur ylide epoxidation reactions, furnishing a novel approach for highly stereoselective synthesis of oxiranes with 98%-100% trans-isomer. The protocol also has excellent yield, convenient workup and recycled starting material. The reason of high trans-selectivity is due to the bulky ferrocenyl sulfide group, which stabilizes the intermediates and determines the trans priority. A possible catalytic mechanism is also proposed.